How USP18 deals with ISG15‐modified proteins: structural basis for the specificity of the protease. (21st September 2017) - Basters, Anja; Knobeloch, Klaus‐Peter; Fritz, Günter
Abstract : The ubiquitin‐specific protease 18 (USP18) has two major functions: (a) it is a highly specific protease that cleaves the ubiquitin‐like modifier ISG15 (interferon‐stimulated gene 15) from proteins, and (b) independent from its enzymatic activity USP18 interacts with the type I interferon receptor and shuts off downstream signaling. The structures of USP18 and a USP18–ISG15 complex revealed the molecular basis of the unique specificity of the protease and might shed some light into its interaction with the interferon receptor. Abstract : The ubiquitin‐specific protease 18 (USP18) is a highly specific protease that cleaves the ubiquitin‐like modifier ISG15 (interferon‐stimulated gene 15) from proteins. USP18 (blue) recognizes ISG15 (green) via a specific surface patch (magenta).